Instability of Detonation Wave at Downstream of Aluminum Crimped Ribbon - Jayan Sentanuhady; Willie Prasidha; Akmal Irfan Majid; Muhammad Akhsin Muflikhun (International Journal of Technology, 2024)
Natural gas is a very reactive fuel that easily causes a detonation wave, especially when the oxidizer is enriched with oxygen or pure oxygen. If the combustion wave is not controlled, a detonation wave can occur, which is dangerous for the safety of workers and industrial facilities. This study was conducted to develop a prototype of a detonation arrester to control detonation waves by using a detonation test tube with a total length of 3000 mm. The characteristics of the combustion wave were evaluated in the present study using a pressure sensor, an ion probe sensor, and a soot track record plate. Results showed that the propagation velocity of the combustion wave and the shock wave pressure increased, whereas the detonation cell size and the reinitiation distance decreased. The experiments performed were able to produce a shock wave pressure that was close to the Chapman–Jouguet pressure. The use of a detonation arrester model could reduce the shock wave pressure and the velocity of the combustion wave. At the initial pressure of the gas mixture of natural gas–oxygen of 10 kPa, the observed combustion phenomenon was deflagration. By contrast, when the initial pressure of the gas mixture of natural gas–oxygen was increased to 20 kPa, the observed combustion phenomenon was detonation quenching.  Furthermore, increasing the initial pressure of the natural gas-oxygen mixture to 30 kPa or higher led to detonation wave propagation as the observed combustion phenomenon.